2009
DOI: 10.1371/journal.ppat.1000361
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-7 Activation by the Nlrc4/Ipaf Inflammasome Restricts Legionella pneumophila Infection

Abstract: Legionella pneumophila (L. pneumophila), the causative agent of a severe form of pneumonia called Legionnaires' disease, replicates in human monocytes and macrophages. Most inbred mouse strains are restrictive to L. pneumophila infection except for the A/J, Nlrc4−/− (Ipaf−/−), and caspase-1−/− derived macrophages. Particularly, caspase-1 activation is detected during L. pneumophila infection of murine macrophages while absent in human cells. Recent in vitro experiments demonstrate that caspase-7 is cleaved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
238
1
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(252 citation statements)
references
References 75 publications
4
238
1
9
Order By: Relevance
“…Cleaved CASP7, as a result of CASP1 activation, has been described for S . Typhimurium [29], L. pneumophila [30] and B. pseudomallei [39] infection, all of which are pathogens predominantly sensed by the NLRC4 inflammasome [16]. Thus, our results demonstrate that CASP1-dependent CASP7 activation is not restricted to the NLRC4 inflammasome.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Cleaved CASP7, as a result of CASP1 activation, has been described for S . Typhimurium [29], L. pneumophila [30] and B. pseudomallei [39] infection, all of which are pathogens predominantly sensed by the NLRC4 inflammasome [16]. Thus, our results demonstrate that CASP1-dependent CASP7 activation is not restricted to the NLRC4 inflammasome.…”
Section: Discussionmentioning
confidence: 76%
“…Because CASP7 (caspase 7) is a known substrate of CASP1 [29,30], we further evaluated if CASP4 affected CASP7 activation. Indeed, B. cenocepacia induced cleavage of CASP7 in WT macrophages, which was significantly reduced in casp4 −/- macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The caspase-1 digestome includes chaperones, cytoskeletal maintenance components and proteins involved in energy metabolism, 37 as well as caspase-7, 38 which has been shown to be activated downstream of NLRC4 inflammasome during bacterial infection. 39 However, it is still not clear why pyroptotic cells die. Permeabilization of the plasma membrane, which presumably participates in protein secretion at early stages of pyroptosis, can be the cause of later cell death due to ruptures caused by cytoplasmic swelling.…”
Section: Immune Surveillance Systems In Plants and Animalsmentioning
confidence: 99%
“…Mice and macrophages lacking caspase-7 allow substantial L. pneumophila replication. It has been shown that caspase-7 is involved in the maturation of L. pneumophila-containing phagosomes and induces cell death in infected macrophages (Akhter et al 2009). In addition, caspase-7 contributes to the activation of NF-jB through the cleavage of PARP1 in response to LPS stimulation in macrophages (Erener et al 2012); however, it is not clear whether this mechanism is involved in the inflammatory response towards genuine bacterial infection.…”
Section: Other Caspasesmentioning
confidence: 99%